New Approaches and Therapeutic Options for Mycobacterium tuberculosis in a Dormant State - Caño-Muñiz, Santiago; Anthony, Richard; Niemann, Stefan; Alffenaar, Jan-Willem C (Clinical microbiology reviews, 2018)
We are far away from the days when tuberculosis (TB) accounted for 1 in 4 deaths during the 19th century. However, complex (MTBC) strains are still the leading cause of morbidity and mortality by a single infectious disease, with 9.6 million cases and 1.5 million deaths reported. One-third of the world's population is estimated by the WHO to be infected with latent TB. During the last decade, several studies have aimed to define the characteristics of dormant bacteria in these latent infections. General features of the shift to a dormant state encompass several phenotypic changes that reduce metabolic activity. This low metabolic state is thought to increase the resistance of MTBC strains to host/environmental stresses, including antibiotic action. Once the stress ceases (e.g., interruption of treatment), dormant cells can reactivate and cause symptomatic disease again. Therefore, a proper understanding of dormancy could guide the rational development of new treatment regimens that target dormant cells, reducing later relapse. Here, we briefly summarize the latest data on the genetics involved in the regulation of dormancy and discuss new approaches to TB treatment.